2007
DOI: 10.1177/1541344607303618
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and Foreign Language Cultural Instruction

Abstract: In a recently published, well-received book, What the Best College Teachers Do, author Ken Bain expounds on 15 years of meticulous research into the attributes and techniques of successful college instructors. One of his main conclusions is that the best college teachers employ what he calls metacognition, or thinking about thinking. He explains that students are inspired when taken on deep intellectual forays. Examples of such cerebral expeditions are probing for tacit assumptions, critically examining the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…More recent work linking transformative learning to FL study has pointed to the language classroom as a rich site for students to question how and why cultures differ. Learning outcomes identified in research on transformative learning in FL learning contexts have included: deepening students’ understanding of culture, both of the target language and of their own (Goulah, 2007; Ivers, 2007; Johnson, 2015; King, 2000; Sosulski, 2013), shifts in how learners view and position themselves to the target language and its cultures (Crane, 2018; Johnson & Mullins Nelson, 2010; Johnson, 2015), and changes in how they see themselves as language learners (Johnson, 2015; King, 2000). In the following, we trace recent L2 learner studies that adopt an explicit transformative learning approach to describe what perspective transformation and their attendant pedagogies may look like in FL instruction.…”
Section: Transformative Learning and Structured Reflectionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent work linking transformative learning to FL study has pointed to the language classroom as a rich site for students to question how and why cultures differ. Learning outcomes identified in research on transformative learning in FL learning contexts have included: deepening students’ understanding of culture, both of the target language and of their own (Goulah, 2007; Ivers, 2007; Johnson, 2015; King, 2000; Sosulski, 2013), shifts in how learners view and position themselves to the target language and its cultures (Crane, 2018; Johnson & Mullins Nelson, 2010; Johnson, 2015), and changes in how they see themselves as language learners (Johnson, 2015; King, 2000). In the following, we trace recent L2 learner studies that adopt an explicit transformative learning approach to describe what perspective transformation and their attendant pedagogies may look like in FL instruction.…”
Section: Transformative Learning and Structured Reflectionmentioning
confidence: 99%
“…In the following, we trace recent L2 learner studies that adopt an explicit transformative learning approach to describe what perspective transformation and their attendant pedagogies may look like in FL instruction. Ivers (2007) argued for the inclusion of critical controversies in the FL curriculum, along with an "ABC theory of self-disturbing," according to which students examine an outside event or circumstance (A), their cultural beliefs regarding such an event (B), and their culturally-conditioned reactions to the event (C). His students were asked to reflect on their responses, and in so doing confront their heretofore-unchallenged assumptions.…”
Section: Language Learning Through a Transformative Learning Lensmentioning
confidence: 99%
See 1 more Smart Citation
“…For adult educators who are in need of practical guidance when working with culturally diverse populations, exploring adult learning through the lens of culture offers the potential to help them understand: (1) the necessity of critically examining one's own and the others' cultural stories (Clover, 2010;Rose-Cohen, 2004;Taylor, 2006;), (2) which sociocultural approaches are the most appropriate to facilitate or guide adult learning (Dass-Brailsford & Serrano, 2010;Sparks, 2002); (3) the importance of developing and maintaining a continuous dialog between one's own culture and others' cultures to assure the success of adult learning (Berry, 2005;Bersch, 2005;Faux, 2004;Hill, 2004;Storrs & Inderbitzin, 2006;Ziegahn, 2001;); and (4) how to incorporate strategies to improve cultural awareness and competency (Barber, 2003;Chang, 2004;Chang, 2007;Clover, 2010;Ewert, 2000;Ivers, 2007;Kerssen-Griep & Eilfer, 2008;MacDonnell & MacDonald, 2011;Smith & Neill, 2005;Vaynshtok, 2001Vaynshtok, /2002.…”
Section: Introductionmentioning
confidence: 99%
“…Genc and Bada (2005) have observed that the dialectical connection between language and culture has always been a concern of L2 teachers and educators and fostered a strong debate with the field. Although that debate was not been settled for decades, Sysoyev and Donelson (2002) and Ivers (2007) allude to the fact that the earlier work by language researchers endorsed the importance and possibilities of including cultural components into L2 curriculum. Pulverness (2003, cited in Genc & Bada, 2005 claimed that a paradigm shift in the debate occurred in the 1970, with a movement away "…from teaching culture based largely on form and structure to a plurality of approaches.. " (p.73) Some studies from the 1990s, for example Byram (1994a;1997a) and Kramsch, Cain & Murphy-Lejeune, 2001) contributed to a better understanding the relationship between learning culture and language.…”
Section: Introductionmentioning
confidence: 99%